2011
DOI: 10.1111/j.1439-0426.2010.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Taste buds on the external body surface and oropharyngeal cavity in Glyptosternon maculatum (Regan, 1905)

Abstract: The aim of the study was to determine the distribution and relative frequency of Glyptosternon maculatum taste buds (TB) using paraffin sectioning, the HE staining method and light microscopy. TBs were found on a variety of surface body areas (lips, barbels, lateral, ventral and dorsal areas, and the dorsal, pelvic, pectoral, anal and adipose fins), as well as in the oropharyngeal cavity. In the epithelium of histological figures of sampled body parts, TB was pear-shaped from the bottom to the top. The ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…According to them the number, distribution and morphological variability of taste buds could be a consequence of adaptation to the environment. Xiong et al () based on histological study, described three types of taste buds, the type I (elevated), type II (slightly elevated), and type III taste buds (not elevated or sunken) on lips, barbels, lateral, ventral and dorsal areas, and the dorsal, pelvic, pectoral, anal and adipose fins, as well as in the oropharyngeal cavity in Glyptosternon maculatum and suggested that these taste buds are in charge of the food selection in an aquatic environment. On the basis of the degree of elevation from the surface, in the oropharyngeal cavity, four types of taste buds in fourteen fish species of the genus Starksia (Fishelson, Baldwin, & Hastings, ) and three types of taste buds in four fish species of the family Kyphosidae, five species of Girellidae and one species of Sparidae have been described (Fishelson, Golanib, & Diamant, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to them the number, distribution and morphological variability of taste buds could be a consequence of adaptation to the environment. Xiong et al () based on histological study, described three types of taste buds, the type I (elevated), type II (slightly elevated), and type III taste buds (not elevated or sunken) on lips, barbels, lateral, ventral and dorsal areas, and the dorsal, pelvic, pectoral, anal and adipose fins, as well as in the oropharyngeal cavity in Glyptosternon maculatum and suggested that these taste buds are in charge of the food selection in an aquatic environment. On the basis of the degree of elevation from the surface, in the oropharyngeal cavity, four types of taste buds in fourteen fish species of the genus Starksia (Fishelson, Baldwin, & Hastings, ) and three types of taste buds in four fish species of the family Kyphosidae, five species of Girellidae and one species of Sparidae have been described (Fishelson, Golanib, & Diamant, ).…”
Section: Discussionmentioning
confidence: 99%
“…Taste buds are greatly developed in fishes and vital for feeding, orientation and social behavior (Boudriot & Reutter, 2001;Xiong et al, 2011). In most fishes, they are not only distributed in the oropharyngeal cavity of the mouth, but also on the basal parts of the gill arches, and they are frequently found in the skin (Fishelson et al, 2004;Xiong et al).…”
Section: Discussionmentioning
confidence: 99%
“…In most fishes, they are not only distributed in the oropharyngeal cavity of the mouth, but also on the basal parts of the gill arches, and they are frequently found in the skin (Fishelson et al, 2004;Xiong et al). Taste buds are the peripheral sense organs of the gustatory system of fish as well as of other vertebrates; they allow animals to recognize food through detection of distinct chemical substances at short distances (Reutter et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The density and localization of taste buds differ even among individuals of the same species (Fishelson et al, 2012). In most fish, taste buds are widely distributed not only in the mouth area but also on the whole‐body surface, and their presence on the body surface allows for easier perception of nutrients (Xiong et al, 2011). Taste buds in fish are divided into three groups according to the depressions or protrusions they make on the epithelium.…”
Section: Introductionmentioning
confidence: 99%